2022
DOI: 10.1155/2022/9933387
|View full text |Cite|
|
Sign up to set email alerts
|

Review on the Effect of Exercise Training on Immune Function

Abstract: Exercise training is not only a necessary means to improve the level of exercise, but also an important means to improve the body’s immunity. Different time, intensity, items, and forms of exercise training have different effects on the body’s immune function. As a double-edged sword to improve the body’s immune function, exercise training is a different reaction mechanism of different immune cells after exercise training. This paper combined with foreign scholars’ studies on the immune function of the body of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Although lack of exercise is considered a major cause of chronic non-communicable diseases [34], physical exertion has been characterized as a double-edged sword for CVD [17,35], endothelial function [36], immune function [37], and arterial thrombosis [38]. There is still controversy on how exercise affects the hemostatic system in healthy individuals, including professional and well-trained athletes, and the effects of exercise on individuals with chronic diseases, including CVD, T2DM, and hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Although lack of exercise is considered a major cause of chronic non-communicable diseases [34], physical exertion has been characterized as a double-edged sword for CVD [17,35], endothelial function [36], immune function [37], and arterial thrombosis [38]. There is still controversy on how exercise affects the hemostatic system in healthy individuals, including professional and well-trained athletes, and the effects of exercise on individuals with chronic diseases, including CVD, T2DM, and hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: The presence of these indicators undermines our confidence in the integrity of the article's content and we cannot, therefore, vouch for its reliability.…”
mentioning
confidence: 99%